A WEB-BASED APPLICATION FOR FILTERING OSN USER WALL - Dani, Pallavi; Andhale, Madhuri; Darade, Aarti; Gupta, Surbhi (IJRDO -Journal of Computer Science Engineering, 2016)
Social networking sites are very popular. It hassocialplatforms,Chats,Gossip,Stories,Advertisements,Audios,Videos and a different types of webbecome a routine for individuals to keep services. Social networking sites share a varietychecking messages on their online social wall. of technical features that allow individuals or theSocial Networking sites are best entertainment users to: built a public profile can also keepfor youngsters. Online social network helps you some contents of profile private visible toto connect with your family,friends, society to selected friends, make a list of other users whoshare your views and ideas on any topic. As share a connection and can see their list ofsocial networking sites are open for all, anyone connections within the system.Basically thesecan post message on their own wall or others visible profiles contains a list of ”friends” thosewall. Sometime people posts inappropriate are also users of that site. A profile is generatedmessages on other's wall which annoys people from obtaining answers of many common andviewing them. Considering this problem our personal intrests questions, such as age, location,paper work is for filtering OSN wall messages interests, etc. Many sites allow users to uploadbefore they reach to the users wall and determine images or pictures, and can also add multimediatrust related to people on OSN.As OSN content to modify the veiw of the profile. e.g.,messages are short for that we used Short text Facebook, allow users to improve their profile byclassification method with trust calculation